1985
DOI: 10.1007/bf02552867
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drainage tube size on adequacy of percutaneous abscess drainage

Abstract: Fifty-one patients with documented abdominal abscess cavities were treated by percutaneous abscess and fluid drainage (PAFD). Drainage catheters made of various materials in sizes ranging from 5 through 18 French (Fr) were retrospectively studied and prospectively assigned to patients. No significant difference in the success or failure of PAFD as a function of these factors was found once an 8.3 Fr catheter with 0.045-inch diameter side-holes was reached; catheters larger than this were not associated with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…Several investigators advocated using a catheter greater than 8.3-French for adequate percutaneous abscess drainage [12,13]. In our series, we used an 8-French pigtail nephrostomy catheter for percutaneous abscess drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators advocated using a catheter greater than 8.3-French for adequate percutaneous abscess drainage [12,13]. In our series, we used an 8-French pigtail nephrostomy catheter for percutaneous abscess drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Critical factors that determine adequate drainage have supposedly been identified decades ago, but many complications related to chest tubes still remain (Millikan et al, 1980;Gift et al, 1991;Mangar et al, 1991;Kollef and Dothager, 1991) Although there have been some comparative physiological and physical studies of the chest drainage tubes (Emerson and McIntyre, 1966;Miller and Sahn, 1987), very little quantitative analysis or evaluation has been performed. Obviously, some suggested that size matters (Gobien et al, 1985;Tattersall et al, 2000). Indeed, tube size and drainage hole size matter in terms of flow rates.…”
Section: Discussionmentioning
confidence: 97%
“…The trochar or 18-gauge Seldinger techniques are inappropriate in smaller children. Catheter sizes less than 8F do not usually provide satisfactory drainage of relatively thick purulent material, but larger catheter sizes do not demonstrate any improved drainage results [10].…”
Section: Discussionmentioning
confidence: 99%